C-Reactive Protein/Albumin Ratio Correlates With Disease Severity and Predicts Outcome in Patients With Aneurysmal Subarachnoid Hemorrhage - Zhang, Dingding; Yan, Huiying; Wei, Yongxiang; Liu, Xiangyu; Zhuang, Zong; Dai, Wei; Li, Jinsong; Li, Wei; Hang, Chunhua (Frontiers in Neurology, 2019)
Aim: The purpose of the present study was to determine if C-reactive protein (CRP)/albumin ratio was associated with disease severity and unfavorable outcome in patients with aneurysmal subarachnoid hemorrhage (aSAH). Methods: One hundred and twenty-three consecutive patients suffering from aSAH were included in the study, which was carried out during the period of June 2016 to September 2018. Clinical and demographic parameters were recorded. CRP and albumin assessments were conducted upon admission. The association of CRP/albumin ratio with the disease severity and 3-month outcomes was evaluated. Results: Higher CRP/albumin ratio was significantly associated with a higher World Federation of Neurological Surgeons Scale (WFNS) grade (p < 0.05). Poor outcome at 3 months was associated with a higher WFNS grade, higher serum glucose, higher CRP level, lower albumin level, higher Fisher score, higher CRP/albumin ratio, symptomatic cerebral vasospasm, intraventricular hemorrhage, delayed cerebral ischemia, and age using univariate analysis. The multivariate binary regression analysis revealed that the CRP/albumin ratio was independently associated with unfavorable outcomes after adjustment for age, WFNS grade, serum glucose, albumin, Fisher score, symptomatic cerebral vasospasm, intraventricular hemorrhage, and delayed cerebral ischemia. Conclusion: Elevated CRP/albumin ratio was associated with disease severity and poor outcomes after aSAH.